Telehealth Training for Surgeons to Empathetically Deliver Bad News Via Video-Mediated Communication. Issue 3 (March 2023) - Rivet, Emily B.; Edwards, Cherie; Lange, Patricia; Haynes, Susan; Feldman, Moshe; Cholyway, Renee
Background: The COVID-19 pandemic resulted in a sudden increase in the need to effectively use telehealth in all realms of health care communication, including the delivery of bad news. Methods: A single arm, unblinded, feasibility study was performed at a tertiary care center located in Central Virginia to explore the value and utility of providing a telehealth training program based on SPIKES to teach surgical residents and faculty best practice for disclosing difficult news via video-mediated communication (VMC). Surgical interns (categorical and preliminary), surgical residents, and surgical faculty from General, Neuro, Pediatric, Plastics, Oncology, Urology, and Vascular surgical specialties were recruited via email to voluntarily participate in a telehealth simulation-based workshop, with 33 surgical learners participating in the training and 28 completing evaluation surveys. Results: Only six respondents (22%) indicated they had prior formal training on telehealth communication with patients or families, while 13 (46%) said they had prior experience giving bad news via telehealth. Comments about improving the training focused on providing more scenarios to practice and more time for feedback. Overall, 25 learners (86%) agreed the activity was a valuable learning experience and the majority (61%) of responses were positive for future use of telehealth for breaking bad news. Discussion: Practicing communication skills with VMC was found to be valuable by surgical interns, residents, and faculty. Formal training should be provided for surgeons at every stage of training and practice to improve skill in the delivery of bad news to patients and their families.